2022
DOI: 10.1180/mgm.2022.25
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of ‘small’ divalent cations (e.g. Mg) for Si and Al in the nepheline tetrahedral framework: 2. The occurrence of Mg-rich nepheline and kalsilite

Abstract: This is a 'preproof' accepted article for Mineralogical Magazine. This version may be subject to change during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Finally, following the calculation method of Henderson and Oliveira (2022), the chemical formula of the highest-Ca nepheline in the Kajishiyama basanite could be written as (Ca 0.467 Ba 0.013 Na , where □ Total is the sum of □ Si and □ Ca . Henderson and Oliveira (2022) and Oliveira and Henderson (2022) reported that K-rich nepheline and kalsilite have a trend including relatively high Mg and Fe 2+ and showed a way to estimate the Fe 2+ proportion in total Fe using the variation of the ΔAl cc (change in T charge minus cavity cation charge: T 3+ + 2T 2+ − M + − 2M 2+ ) and ΔT ch (total analysed T charge minus charge for 16T: 4T 4+ + 3T 3+ + 2T 2+ − 16*mean T charge) stoichiometry parameters. In this study, however, we treated all iron as Fe 3+ because the nepheline of Kajishiyama is low in Mg and Fe, and has a high Na/K ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, following the calculation method of Henderson and Oliveira (2022), the chemical formula of the highest-Ca nepheline in the Kajishiyama basanite could be written as (Ca 0.467 Ba 0.013 Na , where □ Total is the sum of □ Si and □ Ca . Henderson and Oliveira (2022) and Oliveira and Henderson (2022) reported that K-rich nepheline and kalsilite have a trend including relatively high Mg and Fe 2+ and showed a way to estimate the Fe 2+ proportion in total Fe using the variation of the ΔAl cc (change in T charge minus cavity cation charge: T 3+ + 2T 2+ − M + − 2M 2+ ) and ΔT ch (total analysed T charge minus charge for 16T: 4T 4+ + 3T 3+ + 2T 2+ − 16*mean T charge) stoichiometry parameters. In this study, however, we treated all iron as Fe 3+ because the nepheline of Kajishiyama is low in Mg and Fe, and has a high Na/K ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Henderson (2020) concluded that Mg 2+ , Mn 2+ and Ti 4+ replace Si 4+ in the tetrahedral site, and large cations such as Ca 2+ , Ba 2+ and Sr 2+ replace Na + and K + in the cavity sites and suggested a method to calculate the molecular nepheline formula. Henderson and Oliveira (2022) modified that calculation method in order to deal with the presence of Fe 2+ , Mg 2+ and Mn 2+ in tetrahedral sites, and Oliveira and Henderson (2022) proposed a method to estimate Fe 2+ occurrence in nepheline. However, the content and site occupancies of minor and trace elements such as Ca 2+ , Mg 2+ , Mn 2+ , Fe 2+ and Ti 4+ in nepheline have not been studied systematically due to rather limited occurrences of nepheline and the difficulty of preparation of nepheline crystals suitable for detailed structural investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is particularly relevant for Mg- and Fe-rich potassic nephelines and kalsilites and we will consider this matter further in Paper 2 (Oliveira and Henderson, 2022, this volume).…”
Section: Fe Valence Considerationsmentioning
confidence: 99%
“…In addition, different impurities in the composition of nepheline reflect the composition of the mineral-forming medium and physicochemical conditions of the crystallization, which expands the possibilities of using nepheline as a petrological indicator. In particular, Mg-rich nepheline occurs in the groundmass of strongly SiO 2 -undersaturated, feldspar-free, mafic volcanic rocks (olivine-rich foidites) [35]. Hence, the occurrence of Mg-rich nepheline seems to be related to its derivation from Mg-rich magmas.…”
Section: Introductionmentioning
confidence: 99%